2017
DOI: 10.1080/09540121.2017.1332331
|View full text |Cite
|
Sign up to set email alerts
|

Predicting health-related quality of life in people living with HIV in Nepal: mental health disorders and substance use determinants

Abstract: HIV-positive people often experience mental health disorders and engage in substance use. Such conditions tend to impair their health-related quality of life (QOL). Evidence, however, is limited about the influence of mental health disorders and substance use on QOL by gender. Also, little is known about the influences of anxiety and high levels of stress on QOL. We recruited 682 HIV-positive people in Nepal and measured their depression, anxiety, stress levels, substance use, and QOL. Multiple linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“…Consistent with cross-sectional studies in Nepal and Hong Kong, this study found that higher levels of stress were associated with worse HRQoL [ 18 , 48 ]. The fact that HIV-positive individuals experienced higher levels of stress than the general population has been consistently documented by many previous studies [ 49 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with cross-sectional studies in Nepal and Hong Kong, this study found that higher levels of stress were associated with worse HRQoL [ 18 , 48 ]. The fact that HIV-positive individuals experienced higher levels of stress than the general population has been consistently documented by many previous studies [ 49 ].…”
Section: Discussionsupporting
confidence: 87%
“…They also struggle with psychosocial problems such as depression, anxiety, and a lack of social support [ 16 , 17 ]. All these factors may negatively influence HRQoL [ 18 , 19 ]. O’Keefe and Wood found that the majority of decreases in HRQoL, particular in the psychological domain, occurred in early stages of HIV progression [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initial diagnosis may be disruptive for the majority of individuals since they have to face a future life with HIV infection, and struggle with multiple HIV-specific stressors such as stigma, disclosure, psychological adjustment and making treatment decisions [6]. The fact that individuals who perceived higher levels of stress would be more vulnerable to poor HRQoL has been well documented in previous cross-sectional studies [11, 37]. The results from this study further highlighted that stress at the time of diagnosis had a long-term negative impact on HRQoL for at least 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Being married [ 12 , 13 ] or male [ 14 , 15 ] and having good social support [ 16 , 17 ] were positively associated with mental health, social and environmental QoL domains, while being older, homeless, or unemployed tended to negatively affect all QoL domains. Having mental disorders [ 18 ], severe SUD [ 19 ], or comorbidities [ 20 , 21 ], being HIV-positive [ 22 , 23 ], and experiencing trauma symptoms [ 16 , 17 ] negatively affected all QoL domains. Receiving short-term methadone treatment [ 22 ] was positively associated with better QoL across all domains.…”
Section: Introductionmentioning
confidence: 99%